Práticas escolares de matemática no 1º ano do 1º ciclo do ensino fundamental - Nakazawa, Anne Harumi Mizuguchi (2014)
Our research aims to investigate what is taught and how mathematics is taught by teachers of the 1st year of the 1st cycle of Elementary Education. To do the foundation of the text, we reported to the Historical-Cultural Theory and to the principle of the mathematics education in the childhood. To treat the historical-Cultural Theory, we discoursed Vygotsky (2007); Oliveira (1995); Rego (2010); Rigon, Asbahr e Moretti (2010); Moura (2007). To discuss mathematics education in the childhood, we grounded ourselves in the studies of Abrantes, Serrazina e Oliveira (1999); Lanner de Moura (1995); Lopes (2007); Migueis e Azevedo (2007); Moura (2007). The research configures itself in a qualitative approach of the case study kind. To comprehend our problem of investigation, we observed during one semester the classes of mathematics of two effective teachers who work in the 1st year of Elementary Education of two schools in the public system education of the city of Cuiabá. We utilized as instrument for data collecting a questionnaire of identification of the teacher, a semi-structured interview, school documents (Political-Pedagogic Project, annual planning of the 1st year of Elementary Education, students’ notebook and planning notebook of the teachers), the records and observation of mathematics classes. The data of the observation and the record of the classroom were organized in episodes of teaching with the intention of elucidating the movement of the teachers to teach mathematics. To proceed with the analysis, we organized the data in two axes: what they teach and how they teach mathematics. In the axis that deals with “what they teach”, we searched for evidences about what are the mathematics contents worked by the teachers and the conception of mathematics knowledge that it reveals and, in the axis “how they teach”, we searched to investigate the characteristics of the activities proposed, the resources used, the interactions and pedagogic mediation of the teachers. In the analysis of what the teachers teach of mathematics, the contents with the most emphasis are Natural Numbers and the Operations with Natural Numbers and the mathematical knowledge is presented, in most of the pedagogical situations, disregarding the genesis and historicity of the concepts and with no connection with other areas of knowledge. About the axis of ‘how teachers teach’, we considered that the methodology of the teacher A tends to be more centered in repetitive and mechanical exercises, hindering the students to express their personal strategies, the spontaneous record and the development of mathematical thinking. The teacher B presents situations that involve a game and the use of pedagogical materials, besides that, stimulates the argumentation and the exposure of ideas of the students in some moments. However, the process of systematization of activities presents the same characteristics of the teacher A. The data do not indicate that even though the pedagogical work of the teachers are different in some moments, their practices are approximated when do not consider the geneses and historicity of the concept of teaching mathematical concepts, when do not take into consideration the interest and needs of the students, when do not encourage the interactions among students and when the pedagogical mediation characterize itself by the collective orientation about the procedures to be adopted to the resolution of the proposed exercises. The data analysis also take us to consider that there is a need to discuss the articulation between the characteristics of the childhood and the teaching of mathematical content, because we believe the work of mathematics in the 1st year of Elementary Education must consider the historical-cultural process of the development of the concept and this must be articulated to the imagination, fantasy, creation and ludic, characteristics of a life phase of the student of the 1st year of the 1st cycle of Elementary Education is living. So this is possible, the teacher needs to have objective work conditions and the initial and continued formation need to be rethought.